Catalisadores de sílica modificados com nióbio ou alumínio para a conversão de cicloexanona - Daniel Lara Sangiorge (2019)
ε -Caprolactam (CL) is the main precursor of the polymer commonly known as Náilon6. Náilon is a generic name that refers to a series of aliphatic polyamides that have wide applications in the textile industry, the accessories and utilities industry, medical applications, among others. The production process of Caprolactam consists of two main steps. The first step in this production is the cyclohexanone oximation to cyclohexanone oxime, which has as the key process the oxidation of ammonia to hydroxylamine. The second step is the Beckmann rearrangement, which consists of the transformation of the oxime to CL. In this process, fuming sulfuric acid is used as solvent and catalyst, resulting in the production of a large amount of low value ammonium sulfate. To meet the need for large amounts of inorganic acid, the work aims to synthesize and evaluate the action of some catalysts containing both acidic properties and oxidizing properties, so that both process can be done in only one reaction step. The "MCM-41" like silica catalysts were synthesized using tetraethylorthosilicate (TEOS) as a source of silicon and hexadecyltrimethylammonium bromide (CTAB) as a structural agent in alkaline solution. The doped catalysts were made in a similar way, but in addition to the TEOS, niobium nitrates were also used for the SiNb catalyst, 5SiAl, and 15SiAl aluminum nitrates. Regarding the characterizations, the images of MET in conjunction with the low angle XRD show that the organization in hexagonal channels, present in the SiO2 were lost with the addition of aluminum. Adsorption / desorption of N2 showed a decrease of the specific BET area as aluminum was added, which is probably linked to the collapse of the structure. The SiO2 catalyst has presence of mesopores whereas in the doped catalysts, were found only micropores. Although all the catalysts tested were capable of transforming cyclohexanone in both oxime and caprolactam, the best result was with the SiO2 catalyst with 3.6 mols H2O2, which obtained a conversion of 99% and 4% of selectivity.